Effect of catheter ablation with vein of Marshall ethanol infusion for perimitral flutter in a patient with senile transthyretin cardiac amyloidosis: a case report - Fitouchi, Simon; Ohana, Mickael; Cardi, Thomas; Jesel, Laurence; Marzak, Halim (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSenile transthyretin cardiac amyloidosis (AL) is an underdiagnosed infiltrative cardiomyopathy causing heart failure symptoms in elderly patients. It is associated with a higher incidence of atrial fibrillation (AF) and atrial flutter.Case summaryA 75-year-old male patient with senile transthyretin cardiac AL presented with congestive heart failure [New York Heart Association (NYHA) IV] related to rapid perimitral atrial flutter, causing tachycardia-induced cardiomyopathy with a left ventricular ejection fraction (LVEF) of 25%. He underwent AF voltage-guided ablation with vein of Marshall (VOM) ethanol infusion to block the mitral isthmus. Left atrial bipolar voltage mapping revealed diffuse and severe left atrial low-voltage areas related to amyloid protein infiltration within the left atrium (LA). After a 48-month follow-up, no arrhythmia recurrence was observed. Heart failure symptoms improved significantly (NYHA I–II) with an improved LVEF of approximately 45%–50%.DiscussionDiffuse and severe left atrial fibrosis related to amyloid protein infiltration within the LA is generally associated with worse catheter ablation outcomes in cardiac AL patients. This case demonstrated that the VOM ethanol infusion was critical to the success of the catheter ablation procedure, resulting in a better long-term outcome.